2001
DOI: 10.1210/en.142.12.5172
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of ER  with ER  and Progestin Receptor Proteins in the Female Rat Forebrain: Effects of Estradiol Treatment

Abstract: Estrogen and progestin receptors (ER, PgR) play a critical role in the regulation of neuroendocrine functions in females. The neuroanatomical distribution of the recently cloned, ER beta, overlaps with both ER alpha and PgR. To determine whether ER beta is found within ER alpha- or PgR-containing neurons in female rat, we used dual label immunocytochemistry. ER beta-immunoreactivity (ER beta-ir) was primarily detected in the nuclei of cells in the periventricular preoptic area (PvPO), the bed nucleus of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
94
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 0 publications
12
94
0
Order By: Relevance
“…Moreover, variation in the expression of ER-b was not found to be dependent on the concentration of a circulating gonadal steroid (Greco et al 2001). found that the expression of ER-b is negatively correlated with changes in plasma osmolality in males.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, variation in the expression of ER-b was not found to be dependent on the concentration of a circulating gonadal steroid (Greco et al 2001). found that the expression of ER-b is negatively correlated with changes in plasma osmolality in males.…”
Section: Discussionmentioning
confidence: 90%
“…The ER subtypes have unique roles in estrogen-dependent gene regulation and the transcriptional activities of ERα and ERβ differ depending on the cell and tissue context (Hall and McDonnell, 1999). The majority of tissues express predominantly one ER subtype over another, however expression of both ERα and ERβ in the same cell type has been reported for instance in neurons and thymocytes (Greco et al, 2001;Mor et al, 2001). Therefore the presence of both subtypes would predict a more complex regulation of estrogen-mediated gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one possibility is that the protein-protein interactions required for ER␤ signaling are altered with age and the bioavailability of estrogens. Previous studies have shown that ER␤ can associate with traditional coregulators in the brain such as steroid coactivator-1 and estrogen receptor associated protein 140 (5)(6)(7), and that these associations are modified by multiple factors, including age. For instance, one study demonstrated decreased association between estrogen receptor associated protein 140 and ER␤ in the aged hippocampus, despite an overall increase in estrogen receptor associated protein 140 expression (6).…”
mentioning
confidence: 99%